2016
DOI: 10.1016/j.giq.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

E-government design research: Towards the policy-ingrained IT artifact

Abstract: This paper investigates whether design research in e-government should be conducted in some special way compared with standard models for design research. It reviews literature in egovernment and design research in order to generate an answer to this research question. The result of this review affirms that the policy character of e-government should determine the way that such design research is conducted. A tentative e-government design research model, consisting of different activities is formulated. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 62 publications
(90 reference statements)
0
19
0
1
Order By: Relevance
“…The frustrations caused by the learning curve associated with a system may be alleviated by incorporating design principles that support human interoperability, which promotes the inclusion of certain system characteristics during system design that allow human beings to use other similar tools with minimal training, showing some generalizable skills [34]. Human interoperability may be highly intertwined with another concept called cognitive interoperability, which is defined as the human being's way of thinking when using a system [33].…”
Section: Resultsmentioning
confidence: 99%
“…The frustrations caused by the learning curve associated with a system may be alleviated by incorporating design principles that support human interoperability, which promotes the inclusion of certain system characteristics during system design that allow human beings to use other similar tools with minimal training, showing some generalizable skills [34]. Human interoperability may be highly intertwined with another concept called cognitive interoperability, which is defined as the human being's way of thinking when using a system [33].…”
Section: Resultsmentioning
confidence: 99%
“…Adopting CR thereby makes design science more suitable in some areas of research such as e-government. Design science is considered valuable for e-government; however, existing frameworks for design science do not provide specific guidance on how to apply DSR in an e-government context [10]. Following this line of thought, the argumentation made in this paper is illustrated and supported by re-visiting two egovernment DSR projects where success and failure differ depending on the framing.…”
Section: Introductionmentioning
confidence: 87%
“…Constraints (18), (19) and (20) ensure that upgrades (legal, technological or system related) only start in periods that allow them to finish before the end of the planning horizon. Constraint (21) guarantees that a technology upgrade can only finish after the first T T ikh periods as that is the time required to upgrade from one technology to the other. Constraint (22) prevents a procedure from being part of the single window system during the first T V i periods of the planning horizon since that is the time required for its implementation.…”
Section: Design Of a Single Window System For E-government Services 569mentioning
confidence: 99%
“…However, despite the many benefits the implementation of a single window system brings with it, most studies found in the literature focus on the management of the infrastructure and communications that are critical to ensure the availability, effectiveness and efficiency of these systems [15], on how to measure the quality of the services delivered through such systems [47,48], or on how the quality of the services provided through the Internet influence the trust citizens have in public administration [7]. Thus, a multidimensional look, which considers both technological and policy aspects, is essential for the proper design of such systems [21,38].…”
mentioning
confidence: 99%